Functional Analysis of the Hsp93/ClpC Chaperone at the Chloroplast Envelope - Flores-Pérez, Úrsula (Plant Physiol, 2016)
The Hsp100-type chaperone Hsp93/ClpC has crucial roles in chloroplast biogenesis. In addition to its role in proteolysis in the stroma, biochemical and genetic evidence led to the hypothesis that this chaperone collaborates with the inner envelope TIC complex to power preprotein import. Recently, it was suggested that Hsp93, working together with the Clp proteolytic core, can confer a protein quality control mechanism at the envelope. Thus, the role of envelope-localized Hsp93, and the mechanism by which it participates in protein import, remain unclear. To analyze the function of Hsp93 in protein import independently of its ClpP association, we created a mutant of Hsp93 affecting its ClpP-binding motif (PBM) (Hsp93[P-]), which is essential for the chaperone’s interaction with the Clp proteolytic core. The Hsp93[P-] construct was ineffective at complementing the pale-yellow phenotype of hsp93 Arabidopsis (Arabidopsis thaliana) mutants, indicating that the PBM is essential for Hsp93 function. As expected, the PBM mutation negatively affected the degradation activity of the stromal Clp protease. The mutation also disrupted association of Hsp93 with the Clp proteolytic core at the envelope, without affecting the envelope localization of Hsp93 itself or its association with the TIC machinery, which we demonstrate to be mediated by a direct interaction with Tic110. Nonetheless, Hsp93[P-] expression did not detectably improve the protein import efficiency of hsp93 mutant chloroplasts. Thus, our results do not support the proposed function of Hsp93 in protein import propulsion, but are more consistent with the notion of Hsp93 performing a quality control role at the point of import.